Fake truth - Goldberg, Lee, 1962- (Goldberg, Lee, 1962- Ian Ludlow thriller., 2020)
"Author Ian Ludlow writes great adventures, but after helping Chinese movie star Wang Mei defect to the United States, he becomes the accidental hero of a real-life espionage thriller. Now he's stuck with the actress - and suffering a nasty case of writer's block - when he stumbles into a secret Russian plot using "fake news" to outrage Americans into believing a terrifying lie. The only weapon Ian has against the global conspiracy, and the assassins who are closing in on him, is his vivid imagination. If his story isn't a killer thriller, he's dead."--Publisher description.